KAJIAN DOGMATIS TENTANG KONSEP SOCIAL TRINITY LEONARDO BOFF DAN RELEVANSINYA BAGI JEMAAT - Mawuntu , Dewinta Puput; Tamaweol, Roy Dekky (UPT Penelitian Fakultas Teologi Universitas Kristen Indonesia Tomohon, 2024)
A dogmatic study of the Social Trinity can also address individualism that may arise in the congregation. A deeper understanding of this concept can be a way for congregants to better understand the meaning of cooperation, empathy, and support for one another, thus creating a more inclusive and supportive congregational environment. So the researcher used a qualitative research method. Qualitative research is descriptive and tends to use analysis with an inductive approach. The connection between the concept of the Social Trinity and the desired communal life in GMIM Eirene Kema 1 is very real. By contemplating the perichoresis between the persons of God, the congregation is invited to live in a togetherness that is mutually enriching, mutually sustaining, and mutually respectful, both in human relationships and with the universe. It is a way for individuals who share similar beliefs and values to come together and live in close proximity, creating an environment of mutual support and enrichment.